Etika Bertamu dan Menerima Tamu dalam Pesan Rasulullah: Studi Takhrij dan Syarah Hadis - Sulthon Al Hakim Noer Musthofa; Hidayatul Fikra; Dodo Widarda; Hasan Mudis (UIN Sunan Gunung Djati Bandung, 2022)
This research intends to analyze the hadith about adab visiting and accepting it. This research uses a qualitative approach that is emphasized on the study of literature through takhrij methods and hadith sharah. The results of research and discussion show that the hadith of Imam Bukhari No. 5670 about adab visiting and receiving it is of shahih quality based on tinajuan takhrij. As for this hadith sharah shows that for those who visit should be kind to the host, appreciate it and keep the mouth from him. As for the host, the Apostle ordered to entertain guests with good dishes, take care of him if he prayed and maintained his attitude and deeds to the guest. It was an attempt to glorify him as exemplified by the Prophet and the people of shaleh. From this research it can be concluded that the hadith of Imam Bukhari No. 5670 is maqbul (acceptable) and ma'mul (practicable). This study recommends follow-up research with different methods or with different analyses.